Link and Match Strategy Management in Building Graduate Competitiveness - Mashuri, Mashuri; Ballani, Simran; Mehir, Saefuddaulah; Barnawi, Barnawi; Jubaedi, Jubaedi (JURNAL AL-TANZIM, 2024)
This research aims to examine strategic management (Fred R David) link and match (Prosser & Quigley) in growing the competitiveness of graduates through strategy formulation, implementation, evaluation and control. A qualitative approach with a case study method was used in this research. Data collection was carried out through interviews, observation and documentation. Data analysis was conducted using the Miles and Huberman model and then tested through triangulation credibility, transferability, dependability and confirmability. The research results show that Vision and mission, external environmental analysis, future goals, implementation plans, and policies are part of the strategy formation process. The formulation of the link and match strategy involves all interested parties. Implement the link-and-match strategy by optimizing the formation of noble morals and character, increasing competence, optimizing cooperation, and forming entrepreneurship. Strategy evaluation and control are done through review, performance measurement and revision. The implications of this research provide new solutions for educational institutions, especially in increasing the competency of more competitive graduates.